Alleles of the GRF3-2A Gene in Wheat and Their Agronomic Value - Mikhail S. Bazhenov (MDPI AG, 2021)
The Growth-regulating factors (GRF) are a family of plant-specific transcription factors that have roles in plant growth, development and stress response. In this study the diversity of the TaGRF3-2A (TraesCS2A02G435100) gene was investigated in Russian bread wheat germplasm by means of next generation sequencing and molecular markers, and the results compared with those from multiple wheat genome and exome sequencing projects. The results showed that an allele possessing c.495G>T polymorphism found in Bezostaya 1 and designated as TaGRF3-2Ab, is connected with earlier heading and better grain filling under conditions of the Krasnodar Krai. TaGRF3-2Ab is more frequent among Russian winter wheat cultivars than in other germplasms found in the world, implying that it is adaptive for the Chernozem region. A new rare mutation of the TaGRF3-2A was found in the spring wheat cultivar Novosibirskaya 67. The molecular markers developed will facilitate utilization of TaGRF3-2A mutations in future agronomic studies and wheat improvement. Albeit GRF3-2Ab may be good at maintaining high milling quality of the grain, it should be used with caution in breeding of winter wheat cultivars in the perspective of climate change.